A kiskorú gyermek tartásának szabályozása a polgári korban Magyarországon a hatályos szabályozás tükrében - Krausz, Bernadett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
In this article I compare the regulations regarding the maintenance of minor children that are in effect with the legal framework and the judicial practice of Zala County in the civil era, until the end of the Second World War. I will examine the subject through the same aspects and show the differences and the similarities of the two eras. Since the legal situation of minor children born in and out wedlock differed back then, it is also needed to compare their situation.